Phase-Function Normalization in the 3-D Discrete-Ordinates Solution of Radiative Transfer-PART II: Benchmark Comparisons - Hunter, Brian; Guo, Zhixiong (Numerical heat transfer. Part B, Fundamentals, 2012)
Radiative transfer in a cubic enclosure, subject to varying conditions, is determined using the discrete-ordinates method (DOM) with the two normalization techniques introduced in Part I of this study. Their predictions are compared with Monte Carlo simulations. For all cases, false scattering due to directional discretization cannot be corrected when the old technique, which solely conserves scattered energy, is implemented; and thus, significant discrepancies exist when compared to Monte Carlo results. The new technique, which conserves both scattered energy and the asymmetry factor, is able to retain original scattering properties after directional discretization, leading to improved accuracy when compared to Monte Carlo. In addition, a parametric study is presented to gauge the impact of asymmetry-factor conservation on media with various optical properties. Finally, the impact of normalization is investigated for both ultrafast radiative transfer and ballistic incidence with varying incident angle.